2010
DOI: 10.1351/pac-con-09-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Tetradehydrodinaphtho[10]annulene and its transformation into zethrene: A hitherto unknown dehydroannulene and a forgotten aromatic hydrocarbon

Abstract: The synthesis and structural characterization of a hitherto unknown tetradehydrodinaphtho[10]annulene, which had eluded isolation since attempts initiated during the late 1960s, was achieved. Moreover, the dehydroannulene was transformed into stable derivatives of zethrene, which was first reported in 1955, but forgotten for a long time. These molecules are substituted at the 7,14-positions and open the door to the zethrene family for potential application as optoelectronic materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 45 publications
(23 reference statements)
1
44
0
2
Order By: Relevance
“…The validity of this structure–property relationship has been computationally confirmed using various open‐shell singlet models and real compounds including hydrogen atom chains,6, 14, 18 p ‐quinodimethane model,14 diphenalenyl diradicaloids,19, 20 graphene nanoflakes,21–23 and transition metal compounds 24, 25. These results have been also supported by recent experimental data on two‐photon absorption26 and third harmonic generation,27 and they have stimulated other investigations on linear and NLO properties28–39 of multiradical compounds as well as their vibrational signatures 40, 41. In previous studies,20, 42, 43 spin‐unrestricted hybrid density functional theory (UDFT) calculations have shown that supermolecular and supramolecular multiradical systems composed of phenalenyl units are promising NLO systems, because their properties can be controlled by adjusting the architectures, the diradical characters, and the charge states.…”
Section: Introductionsupporting
confidence: 64%
“…The validity of this structure–property relationship has been computationally confirmed using various open‐shell singlet models and real compounds including hydrogen atom chains,6, 14, 18 p ‐quinodimethane model,14 diphenalenyl diradicaloids,19, 20 graphene nanoflakes,21–23 and transition metal compounds 24, 25. These results have been also supported by recent experimental data on two‐photon absorption26 and third harmonic generation,27 and they have stimulated other investigations on linear and NLO properties28–39 of multiradical compounds as well as their vibrational signatures 40, 41. In previous studies,20, 42, 43 spin‐unrestricted hybrid density functional theory (UDFT) calculations have shown that supermolecular and supramolecular multiradical systems composed of phenalenyl units are promising NLO systems, because their properties can be controlled by adjusting the architectures, the diradical characters, and the charge states.…”
Section: Introductionsupporting
confidence: 64%
“…Dibenzo[de,mn]naphthacene (zethrene, 1 a, R= H) is a member of the benzenoid hydrocarbon family, [1] and has an interesting structure with respect to the formal definitions of aromaticity. The central two six-membered rings in zethrene (1 a) cannot present aromaticity associated with the KekulØ structure.…”
mentioning
confidence: 99%
“…Based on formal definitions of aromaticity, dibenzo‐[ de , mn ]naphthacene (zethrene, 21 ) has an interesting structure . The central two six‐membered rings in 21 cannot account for the aromaticity associated with its Kekulé structure.…”
Section: Zethrenes and Pyrroloarenesmentioning
confidence: 99%
“…The central two six‐membered rings in 21 cannot account for the aromaticity associated with its Kekulé structure. Zethrene and its derivatives were predicted to exhibit novel physical properties, which may have potential applications in electroluminescent devices and organic transistors …”
Section: Zethrenes and Pyrroloarenesmentioning
confidence: 99%